2019
DOI: 10.1186/s12970-019-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the FTO gene polymorphisms (rs1421085, rs17817449 and rs9939609) in exercise-trained men and women: the effects of a 4-week hypocaloric diet

Abstract: Background Variations in the fat mass and obesity-associated gene (FTO) are associated with obesity; however, it is unclear if changes in energy intake affect the adaptive response to caloric restriction in those with risk variants. The three FTO single nucleotide polymorphisms (SNPs), rs1421085, rs17817449 and rs9939609, are in strong linkage disequilibrium. Thus, the purpose of this investigation was to determine the role of these FTO SNPs vis-à-vis the effects of a 4-week hypocaloric diet on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Further studies to validate the conclusions using the promotion product InBody 770 should be performed. 38 In conclusion, it is necessary to identify visceral obesity in patients with gastric cancer both prior to surgery and in the aftercare period via body composition analysis. The present study revealed that the VFA measured by CT and BIA showed significant correlation and satisfactory reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies to validate the conclusions using the promotion product InBody 770 should be performed. 38 In conclusion, it is necessary to identify visceral obesity in patients with gastric cancer both prior to surgery and in the aftercare period via body composition analysis. The present study revealed that the VFA measured by CT and BIA showed significant correlation and satisfactory reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies to validate the conclusions using the promotion product InBody 770 should be performed. 38 …”
Section: Discussionmentioning
confidence: 99%
“…12 Using these search criteria we identified 183 records dating from 1994-2019, and of these, 158 records were removed for not meeting the inclusion criteria. Additional search tools (ie, searching relevant search terms through Google Scholar and hand-searching reference lists of identified papers) were used to add 5 additional records, 8,[13][14][15][16] and this resulted in a total of 30 scientific studies containing relevant criteria. [6][7][8] From these studies, 20 gene candidates were identified, and of these, the 10 polymorphisms present on the array were interrogated in the current study (Table 1).…”
Section: Participants and Training Regimensmentioning
confidence: 99%
“…FTO gene has an important role in regulation of food intake, energy balance, appetite, and basal metabolic rate (BMR) [ 11 , 12 ]. Polymorphisms in the intron regions of FTO gene may act as a regulator of other genes such as Iroquois homeobox 3 ( IRX3 ) and obesity-associated single nucleotide polymorphisms of FTO were associated with expression of IRX3 , but not FTO , in human brains [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the intron regions of FTO gene may act as a regulator of other genes such as Iroquois homeobox 3 ( IRX3 ) and obesity-associated single nucleotide polymorphisms of FTO were associated with expression of IRX3 , but not FTO , in human brains [ 11 ]. On the other hand, FTO genotypes may influence the association of dietary macronutrients with Body Mass Index (BMI), body weight, food intake, energy balance, appetite, and hormone secretion [ 12 14 ]. Dietary macronutrients including carbohydrate, fat, and protein, as the main sources of energy, play key roles in regulation of body weight and BMI [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%